PERLINDUNGAN HUKUM TERHADAP PERAWAT DALAM MELAKUKAN TINDAKAN MEDIS - Sukindar, Sukindar (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2017)
Doctors are one of the main components of health care providers to the public who are allowed to perform medical actions. One health worker who contributes to the improvement of health status is a nurse, who has limited duty to provide nursing care and has no authority to perform medical actions, except in an emergency and there is a transfer from the doctor. In order to protect the duty of the nurse in performing medical acts, it is necessary to have the delegation of authority in writing as regulated in Law Number 29 Year 2004 concerning Medical Practice, Law Number 38 Year 2014 on Nursing and its implementation regulation is regulated in Article 15 of Decree of the Minister of Health Number 1239 of 2001 Regarding Registration and Nurse Practice and Regulation of the Minister of Health No. 2052 / Menkes / Per / X / 2011 About Practice License and Implementation of Medical Practice.This paper aims to analyze and explain in detail the Legal Protection Against Nurses  in  Conducting  Medical  Measures  as  well  as  the  Doctor's  Delegation  of Authority Mechanisms to Nurses in Medical Measures. By using normative juridical research methods, the results of this paper are expected to contribute thoughts to Doctors and Nurses to increase knowledge about the law and can provide a detailed explanation regarding the application of roles and functions of the boundaries of the authority of health personnel concerned in accordance with applicable provisions.